Comparative Assessment of Familiarity/Novelty Preferences in Rodents - Beery, Annaliese K.; Shambaugh, Katharine L. (Frontiers in Behavioral Neuroscience, 2021)
Sociality—i.e. life in social groups—has evolved many times in rodents, and the nature of these social groups varies considerably. While species-typical behaviors have been described for many species in field settings, the use of consistent behavioral assays in the laboratory provides key data for comparisons across species. The preference for interaction with familiar or novel individuals is a particularly important dimension of social behavior. Familiarity preference in particular may be associated with more closed, less flexible social groups, and the spectrum of group structure from selective to gregarious has been used as a characteristic feature in classification of group types. Laboratory tests of social choice range from brief (10 min) to extended (e.g. 3hr); familiarity preferences typically need long testing intervals to manifest. We used three-hour peer partner preference tests to test for the presence of familiarity preferences in same-sex cage-mates and strangers in rats. We then conducted an aggregated analysis of familiarity preferences across multiple rodent species (rats, mice, prairie voles, meadow voles, and degus) we had previously collected using the same protocol. We found a high degree of consistency within species across studies, supporting the existence of strong, species-typical familiarity preferences in prairie voles and meadow voles, and a lack of familiarity preferences in all other species tested. Sociability, or total time spent near conspecifics, was unrelated to selectivity in social preference. These findings provide important background to interpreting differences in neurobiological mechanisms involved in social behavior in these species.